Durvalumab in NSCLC: latest evidence and clinical potential. (October 2018) - Muñoz-Unceta, Nerea; Burgueño, Isabel; Jiménez, Elizabeth; Paz-Ares, Luis
Advances in immunotherapy have led to radical improvements in outcomes, including overall survival, such as in non-small cell lung cancer (NSCLC) patients with metastatic disease treated with immune checkpoint inhibitors. More recently, promising results have been obtained in earlier disease settings, and combinations with other therapies are being actively investigated. Durvalumab, a monoclonal antibody directed against the programmed death ligand 1, has demonstrated significant activity in NSCLC, including increased progression-free survival rates after chemoradiation for unresectable stage III disease, with a favourable safety profile. Clinical trials, including phase III studies, are ongoing as monotherapy and in combination with chemotherapy, radiotherapy and other immunotherapies, such as the anti-cytotoxic T-lymphocyte antigen 4 drug tremelimumab, in diverse stages of the disease.